The Vietnamese Communist Mommittee of the Ho Chi Minh ideology on cadre work - Bùi Thị Bích Thuận (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Cadre work is always a very important factor in determining the success of revolutionary cause. Thus, during his revolutionary life, Ho Chi Minh always paid special attention and expressed his views on the work of cadres. Based on Ho Chi Minh's ideas and objective demands of the revolutionary leadership, the Communist Party of Vietnam always attaches great importance to building a contingent of qualified and capable cadres.